Antibacterial activity and mechanism of Litsea cubeba essential oil against methicillin-resistant Staphylococcus aureus (MRSA) - Hu, Wei; Li, Changzhu; Dai, Jinming; Cui, Haiying; Lin, Lin (Industrial crops and products, 2019)
•Litsea cubeba essential oil showed good antibacterial effects on MRSA.•Litsea cubeba essential oil could break MRSA cell membrane.•Litsea cubeba essential oil could inhibit the HMP of MRSA.•Litsea cubeba essential oil could react with DNA in the form of chimera. Litsea cubeba essential oil (LC-EO), one of the natural essential oils, could gradually replace chemical synthesis food additive in food industry due to its good antimicrobial activity. However, the antibacterial mechanism of the LC-EO is uncertain. This study took methicillin-resistant staphylococcus aureus (MRSA) as the research object to exposit its antibacterial mechanism. Research findings indicated the destructive effect of LC-EO on MRSA cell membrane, leading to intracellular biological macromolecules leakage. What’s more, the Hexose Monophophate Pathway (HMP) and its key enzyme (glucose-6-phosphate dehydrogenase) activity of MRSA were also inhibited after LC-EO treatment. Finally, the UV absorption spectroscopy result revealed that the key component of LC-EO (citral) could react with DNA in the form of chimera.